Brain atrophy in heart failure patients following left ventricular assist device implantation or heart transplantation - D.Alan Herbst, MD; Banafsheh Shakibajahromi, MD; Michael V. Genuardi, MD; Amit Iyengar, MD; Dawn Mechanic-Hamilton, PhD; H. Branch Coslett, MD; Pavan Atluri, MD; Christopher G. Favilla, MD (JHLT Open)
Advanced heart failure is associated with accelerated brain atrophy, largely related to chronic cerebral malperfusion. Both heart transplantation (HT) and left ventricular assist device (LVAD) implantation improve vital organ perfusion, but the comparative effect on brain atrophy remains unclear. Given the MR incompatibility of LVADs, we leveraged serial CT imaging in patients who underwent either HT or LVAD implantation. 58 patients were included in this single-center retrospective cohort (23 LVAD; 35 HT). LVAD patients experienced greater brain atrophy (median: 7.1 mL/year; IQR: 0.9–15.7) than transplant patients (median: 0.4 mL/year; IQR: −6.7–13.9), but this difference was non-significant (p=0.09). Temporal atrophy (expansion of the Sylvian fissure) was greater in LVAD patients (median: 0.91 mm/year; IQR: 0.14–2.27) than HT patients (median: 0.10 mm/year; IQR: 0.02–0.55), p=0.005. These observations reveal a need for future work to prospectively quantify brain atrophy after LVAD implantation and HT, while comparing with that of advanced heart failure.